Rational Design of WSe2/WS2/WSe2 Dual Junction Phototransistor Incorporating High Responsivity and Detectivity. Issue 9 (24th July 2022) - Luo, Zhongtong; Yang, Mengmeng; Wu, Dongsi; Huang, Zihao; Gao, Wei; Zhang, Menglong; Zhou, Yuchen; Zhao, Yu; Zheng, Zhaoqiang; Li, Jingbo
Abstract: The excellent semiconducting properties and ultrathin morphological characteristics allow van der Waals (vdW) heterostructures based on 2D materials to be promising channel materials for the next‐generation optoelectronic devices, especially in photodetectors. Although various 2D heterostructure‐based photodetectors have been developed, the unavoidable trade‐off between responsivity and detectivity remains a critical issue for these devices. Here, an ingenious phototransistor based on WSe2 /WS2 /WSe2 dual‐vdW heterostructures is constructed, performing both high responsivity and detectivity. In the charge neutrality point (gate voltage of −15 V and bias voltage of 1 V), this device demonstrates a pronounced photosensitivity, accompanying with high detectivity of 1.9 × 10 14  Jones, high responsivity of 35.4 A W −1, and fast rise/fall time of 3.2/2.5 ms at 405 nm with power density of 60 µW cm −2 . Density functional theory calculations, energy band profiles, and optoelectronic characteristics jointly verify that the high performance is ascribed to the distinctive device design, which not only facilitates the separation of photogenerated carriers but also produces a strong photogating effect. As a feasible application, an automotive radar system is demonstrated, proving that the device has considerable potential for application in vehicle intelligent assisted driving. Abstract : An ingenious phototransistor based on WSe2 /WS2 /WSe2 dual‐van der Waals heterostructures is constructed, performing both high responsivity, light on/off ratio and detectivity in the charge neutrality point. This high performance is ascribed to the distinctive device design, which not only facilitates the separation of photogenerated carriers but also produces a strong photogating effect.